Assessment of root canal morphology of mandibular central incisor in Indian population - Sharma, Ankita; Thakur, Anamika; Malhotra, Aayush; Kaur, Sunpreet; Bansal, Abhishek; Kukreja, Navneet (International Journal of Psychosocial Rehabilitation, 2020)
Background: The root canal anatomy of each tooth has certain commonly occurring characteristics as well as numerous atypical ones. The present study was conducted to assess root canal morphology of mandibular central incisors. Materials & Methods: The present in invitro study was conducted on 60 extracted mandibular central incisors. Following this, biomechanical preparation was done, and tooth sectioning was done. The samples were evaluated using a stereomicroscope under 10X magnification. The number of root canals and the type of canals based on Vertucci’s classification. Results: 1 canal was seen in 45 (75%) and 2 in 15 (25%) samples. Type I canal was seen in 54%, type III in 35%, and type V in 11%. The difference was significant (P< 0.05). The shape of the canal at 1 mm was oval in 50%, round in 41%, and long oval in 9%; at 2 mm, round in 17%, oval in 62%, long oval in 18%, and ribbon in 3%; and at 3 mm, round in 16%, oval in 42%, long oval in 27%, and ribbon-shaped in 15%. The difference was significant (P< 0.05). Conclusion: Authors found that most common shape of the canal was oval, seen at different levels and type was type I